The Société de radiodiffusion de la France d'outre-mer. Birth of a Franco-African radio broadcasting empire at the time of decolonization (1939-1969) - (:unkn) unknown (My University, 2023)
Until the end of the 1940's, France leans very few on radiobroadcasting to enforce its hold on the colonized populations of sub-Saharan French Africa (AOF, AÉF and Madagascar). It's at the last moment that France managed to redress the situation. A radiobroadcasting network managed from Paris was built in a few years. This network has been entrusted to the Société de Radiodiffusion de la France d'outre-mer (SORAFOM), created in 1956 by Pierre Schaeffer, inventor of the “musique concrete”. This creation, so fragile in appearance, managed to resist decolonization. It even had its golden age during the 1960's. The activities of the Office de Coopération radiophonique (OCORA), witch replaced the SORAFOM in 1962, extended to television and all branches of radio: provision of programs, specialists, equipment, training of Africans in its Studio-École. The society founded by Pierre Schaeffer intervened even in more countries than before independence. France has thus succeeded in building a media empire in Africa whereas the formal empire collapsed. This PHD propose to enlighten this apparent paradox by relying on unpublished or little-used sources. Its proposes to answer some burning questions. Which stakeholders are at the origin of this empire? What were their intentions? Why the SORAFOM-OCORA has survived the independence of African countries? To what extent was this company a tool of French imperialism before and after independence ? What were the human and cultural consequences of the formation of this media empire?
Keywords: African Research